Аўтабіяграфічная аповесць Развітанне з ілюзіямі: Васіль Быкаў вачыма Аляксея Карпюка - Sakowicz, Anna (Acta Polono-Ruthenica, 2018)
This article analyses the memories about Wasyl Bykow (1924–2003), one of the most outstanding Belarusian prose writers Aleksy Karpiuk (1920–1992) included in the book Farewell to Illusions (2007). Particular attention is paid to the writer’s life in Grodno and his friendship with A. Karpiuk, an artist born in Straszewo in the Bialystok region, the author of many works describing the reality of the borderland of north-eastern Poland. A. Karpiuk truly describes twenty-two years shared with his friend in Grodno, in a period unfavorable for rebellious writers. The writer shows the personality of Bykow, focuses on the socio-political aspect of life in the second half of the twentieth century, but tactically ignores the private sphere. A. Karpiuk, on the occasion of describing the problems that the literary milieu struggled with, gives his own assessment of the socio-political situation in Belarus.